New measurements and modeling of high pressure thermodynamic properties of glycols - Crespo, E.A. (Elsevier B.V., 2017)
New experimental density data of six glycols, namely ethylene glycol (EG), diethylene glycol (DEG), triethylene glycol (TriEG), tetraethylene glycol (TeEG), pentaethylene glycol (PeEG) and hexaethylene glycol (HeEG), and a polyethyleneglycol (PEG 400) were determined in a wide range of temperatures (283–363 K) and pressures (0.1–95) MPa. The experimental density data was first correlated, as function of temperature and pressure, using the modified Tait-Tammann equation, and the derivative properties, such as isobaric thermal expansion coefficients and the isothermal compressibility, were estimated. It is shown that the isobaric thermal expansivity converges to a cross-over point that, although commonly observed for non-associating compounds, is here reported for the first time for the studied glycols. This denotes the presence of hydrogen bonds, mainly dominated by dispersive interactions, breaking and decreasing intermolecular interactions as the temperature and the number of glycols ethoxy groups increase. The study is completed with the modeling of the experimental data using the soft-SAFT equation of state. A molecular model, considering the glycol molecules as LJ chains with one associating site at each of the compounds' end groups (hydroxyl groups) is proposed for all the glycols, allowing the EoS to provide an excellent description of the glycols pVT surface. Additionally, the optimized parameters were correlated with the compound's molecular weight, providing a good prediction of the PEG400 density and the compounds' derivative properties. © 2017 Elsevier B.V.